Susceptibility of Vicia sativa Cultivars to an Oncogenic Strain of Agrobacterium tumefaciens - Aziz Karakaya (Journal of Agricultural Sciences)
Agrobacterium tumefaciens is commonly used in gene transfer to plants. Determination of the suitable plant genotypes facilitate this process. İn this study, eight common vetch cultivars grown in Turkey were assessed for their susceptibility to oncogenic Agrobacterium tumefaciens strain A281 Ali common vetch cultivars showed susceptibility to infection from A. tumefaciens strain A281.